Review: Perspectives on the European Videogame - Andre Cowen (Press Start, 2023)
Review: Perspectives on the European Videogame, edited by Victor Navarro-Remesal and Óliver Pérez-Latorre. 2021. Amsterdam University Press. 236 pp.